"Honoring Somebody that Society Doesn't Honor": Therapists Working in the Context of Poverty. Issue 2 (20th December 2012) - Smith, Laura; Li, Vanessa; Dykema, Stephanie; Hamlet, Danae; Shellman, Alison
<x xml:space="preserve">Abstract</x> Although it has been widely acknowledged that people living in poverty are underserved by mental health professionals, little is known about the experiences of psychotherapists who are currently working with poor clients. What can we learn from these clinicians that may help us more effectively prepare trainees for work in the context of poverty? This qualitative investigation analyzed narrative data from 10 therapists regarding their work with poor clients. Participants revealed perceptions of the challenging (and rewarding) nature of this work, the inadequacies of their training to meet these demands, and the damaging influence of social stigma within their clients' lives and presenting problems, as well as on clinicians' own occupational status.